Microscopic Colitis: Epidemiology, Pathophysiology, Diagnosis and Current Management—An Update 2013. (18th April 2013) - Storr, Martin Alexander
Abstract : Microscopic colitis is a common cause of chronic diarrhea. Over the last years the incidence and the prevalence of microscopic colitis are rising and this rise is largely attributed to a rising awareness, and concomitantly an increasing number of diagnoses are made. Patients with microscopic colitis report watery, nonbloody diarrhea of chronic, intermittent, or chronic recurrent course. Following an unremarkable physical examination the diagnosis of microscopic colitis is made by colonoscopy, which shows essentially a normal colonic mucosa. Biopsies taken during the colonoscopy procedure will then finally establish the correct diagnosis. Histological workup can then confirm a diagnosis of microscopic colitis and can distinguish the two distinct histological forms, namely, collagenous colitis and lymphocytic colitis. Presently both forms are diagnosed and treated in the same way; thus the description of the two forms is not of clinical value, though this may change in future. Depending on the patients age and gender 10–30% of patients investigated for chronic diarrhea will be diagnosed with microscopic colitis if biopsies are taken. Microscopic colitis is most common in older patients, especially in female patients and is frequently associated with autoimmune disorders and the consumption of several drugs. This review summarizes the present knowledge of the epidemiology, the pathophysiology, and the diagnosis of microscopic colitis and discusses the former and the present treatment options.